Enhancing care for people living with HIV: current and future monitoring approaches. Issue 4 (3rd April 2021) - Maggiolo, Franco; Bandera, Alessandra; Bonora, Stefano; Borderi, Marco; Calcagno, Andrea; Cattelan, Annamaria; Cingolani, Antonella; Gianotti, Nicola; Lichtner, Miriam; Lo Caputo, Sergio; Madeddu, Giordano; Maggi, Paolo; et al.
ABSTRACT: Introduction: Antiretroviral therapy (ART) is the most significant advance in the medical management of HIV-1 infection. Given the fact that HIV cannot be eradicated from the body, ART has to be indefinitely maintained. New approaches need to be defined for monitoring HIV-infected individuals (PLWHIV), including clinical, virologic, immunological parameters and also ways to collect individual points of view and quality of life. Areas covered: We discuss which tests may be used to improve the management of PLWHIV and respond to a comprehensive health demand. Expert opinion: Viral load and CD4 counts are well-validated outcome measures and we still need them, but they do not completely depict the health status of PLWHIV. We need to better understand and to apply to clinical practice what happens in sanctuaries, what is the role of HIV DNA, what is the meaning of low-level viremia. Most of these questions do not yet have a definitive response. Further, we need to understand how to modify these variables in order to improve outcomes. Similar points may be raised for immunological measures and for tests exploring the tolerability of drugs. The goal must be the evolution from a viro/immunologic-based to a comprehensive quality-of-health-based evaluation of PLWHIV.